Banking governance and the extent of application of its principles to prevent administrative corruption in Libyan banks. "A field study from the point of view of employees of banks operating in Murzuq" - Mohamed Almabrouk Khalifah Rajab & Abdullah AlSenussi Mihoub (Journal of Pure & Applied Sciences, 2020)
In this study, we reviewed the nature of governance in Libyan commercial banks, the extent to which it applies to corporate governance and its principles, the causes of administrative corruption and ways to prevent it, and the respondents ’view of governance and its principles, and the problem of the study has been formulated the question that says does the commitment to apply the principles of banking governance lead to the prevention of administrative corruption within the institution ?, As this study aimed to shed light on what governance is and its principles and the extent to which the concerned banks apply the principles of governance to protect against administrative corruption, A number (70) questionnaire forms were distributed to the respondents, and the returned forms reached (50) forms, and they were found to be subject to statistical analysis. and that this study concluded that the banks under study are concerned with banking governance and that they adhere to implementing its principles and considers them an effective tool to reduce the abuse of the position and combat bribery and administrative corruption Of all kinds, The study also recommends the need to pay attention to the issue of governance within financial institutions (banks), because of its role in combating the phenomenon of administrative corruption, as well as working to give training courses to emphasize the importance of banking governance, so that it will be the basis for the work of these banks.